Air pollutant dispersion using advection-diffusion equation (Nepal Journal of Environmental Science, 2024)
The advection-diffusion model is one of the mathematical models that may be used to understand how air pollutants are spread in the environment. It uses the advection-diffusion system with time-dependent prediction of the spread of environmental contamination under various environmental conditions to determine whether the contaminants are more concentrated at ground level or close to the point of emissions. The times, diffusivity, emission sources, and wind profile are all considered by the model. In order to determine the approach’s descriptive characteristics in terms of advection and dispersion coefficients, we evaluate the exact solution to a flow field problem as an initial value problem in space.